Variance Components and Association Between Grain Yield and its Component in Pearl Millet - Dubey, L K; Manga, V K (Annals of Arid Zone, 2016)
Variability, correlation and heritability were studied in 45 genotypes of pearl millet. The genotypic (GCV) and phenotypic (PCV) coefficients of variation were higher for grain yield and ear head weight. The PCV were higher than the GCV for all the characters studied. High genetic advance afong with high percentage of broad sense heritability were observed for ear head weight and dry fodder weight. The grain yield was negatively correlated with days to 50% flowering where as it was positively and significantly correlated with number of ear heads per plot and ear head weight.